Molybdenum-Mediated One-Pot Synthesis of 2-Hydroxypyrimidines from Isoxazoles - Rochelle, Servane; Beaumont, Stéphane (Synthesis, 2023)
A one-pot procedure towards substituted 2-hydroxypyrimidines from commercially available isoxazoles is reported. The process involves cleavage of the isoxazole N–O bond mediated by Mo2(OAc)4, then in situ hydrolysis of the resulting β-amino enone to the reactive 1,3-dicarbonylated intermediate, followed by hydroxypyrimidine formation in the presence of urea. Moderate to excellent yields are obtained, leading to functionalized hydroxypyrimidines. By using readily available isoxazoles, a wide range of new diverse polysubstituted hydroxypyrimidines may be prepared by this method.
Keywords: isoxazoles; N–O bond cleavage; hydroxypyrimidines; molybdenum; one-pot; β-amino enones; 1,3-diketones